Repeatability of Baseline Corticosterone and Acute Stress Responses to Capture, and Patterns of Reproductive Hormones in Vitellogenic and Non‐Vitellogenic Female Fijian Ground Frog (Platymantis vitiana). Issue 8 (11th July 2013) - Narayan, Edward J.; Hero, Jean‐Marc
ABSTRACT The survival of animal species and individuals is largely determined by their ability to express physiological stress responses to predictable and unpredictable environmental challenges. Currently, there is no empirical evidence presenting the stress endocrine responses of female frogs during breeding between different reproductive groups. In this study, non‐invasive urine sampling and standard capture and handling protocol were used to quantify baseline and short‐term corticosterone stress responses in vitellogenic and non‐vitellogenic female Fijian ground frog (Platymantis vitiana) during the annual breeding period. Urinary estrogen and progesterone metabolites were also quantified in the same frog urine samples. Repeated sampling of the female frogs (n = 20) on three occasions enabled repeatability (r) of reproductive and stress hormones to be quantified. All female frogs generated urinary corticosterone responses to the standard capture and handling stressor. Both baseline and short‐term corticosterone responses were significantly higher in magnitude in the vitellogenic females in comparison to the non‐vitellogenic female frogs. Vitellogenic females also showed significantly higher levels of urinary estrogen and progesterone metabolites in comparison to the non‐vitellogenic females. Baseline urinary corticosterone, short‐term corticosterone responses, urinary estrogen, and progesterone metabolites were highly repeatable for both female groups. The results highlight the importance of reproductive and stress hormones during the breeding period in female ground frogs. Future studies should determine the role of potential biological stressors (such as interactions with invasive species) that could be mediating the observed differences in stress endocrine responses of the vitellogenic and non‐vitellogenic female frogs. J. Exp. Zool. 319A: 471–481, 2013. © 2013 Wiley Periodicals, Inc.